Balancing Act: how Militant Groups Manage Strategic and Ideological Resources - Chesterton, Hannah (Perspectives on terrorism, 2024)
What happens when militant groups must choose between logistical needs and ideology, and how does that trade-off impact subsequent violence? Many groups balance both strategic and psychological considerations but ultimately weigh one more heavily than the other. We propose a typology based on this trade-off between logistical and ideological resources and the degree of violence against civilians. We propose that combination produces four overarching ideal types: violent militants, militant opportunists, professional militants, or disciplined militants. We conduct a plausibility probe of the types and propose a model of how groups re-produce violence patterns once established. The four cases - the Weather Underground, al-Qaeda in Iraq, the Revolutionary United Front, and autodefensas in Mexico - are extreme cases that vary in their calculus of logistics versus ideology and their degree of violence. We find that all types go through a standard process to establish and perpetuate their approach to violence. In addition, groups experience different advantages and pitfalls based on their trade-off calculus. An ideological emphasis is typically accompanied by greater oversight of recruitment and tactics, but groups that become too ideologically rigid risk collapsing from organisational problems and difficulties connecting with their constituents. Conversely, those that weigh logistical considerations more heavily have less oversight over recruitment, which increases their risks of infiltration by opportunists and criminals.